Filmowanie klasyka w podzielonych Niemczech: kinowe adaptacje Bertolta Brechta - Gwóźdź, Andrzej (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article discusses the presence of Bertolt Brecht’s plays and prose in film culturesof two antagonistic German states (the German Democratic Republic andthe Federal Republic of Germany) between 1949 and 1989. The author focuses onthe ways of transferring works (and media) within these cultures. He indicates thefilm version of Mother Courage and Her Children (Mutter Courage und ihre Kinder,dir. Peter Palitzsch, Manfred Wekwerth, GDR 1960) and Three Penny Opera(Die Dreigroschenoper, dir. Wolfgang Staudte, FRG–France 1963) as basic examplesof different testimonies of reception of Brecht’s deeds in two German states(a classicising attitude and the one inscribed in popular culture). Referring to theHistory Lesson (Geschichtsunterricht, FRG–Italy 1972) by Jean-Marie Straub andDanièle Huillet the author identifies the presence of the New German Cinema infilm reading of Brecht’s works. Film culture of the GDR is marked by significantDEFA-adaptation of the short stories: Zwei Söhne (Two Sons) (dir. HelmutNitzschke, a part of the novella film Aus unserer Zeit (Our time, GDR 1969) whichis discussed in the context of the actors tradition of the Brechtian theatre.